2002
DOI: 10.1111/1468-0262.00340
|View full text |Cite
|
Sign up to set email alerts
|

Swapping the Nested Fixed Point Algorithm: A Class of Estimators for Discrete Markov Decision Models

Abstract: This paper proposes a new nested algorithm (NPL) for the estimation of a class of discrete Markov decision models and studies its statistical and computational properties. Our method is based on a representation of the solution of the dynamic programming problem in the space of conditional choice probabilities. When the NPL algorithm is initialized with consistent nonparametric estimates of conditional choice probabilities, successive iterations return a sequence of estimators of the structural parameters whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
338
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(350 citation statements)
references
References 28 publications
8
338
0
1
Order By: Relevance
“…1 For related methods in the single agent context see Hotz and Miller (1993), Hotz et al (1994), and Aguirregabiria and Mira (2002). For a review of structural estimation of dynamic games see Ackerberg et al (in press).…”
Section: Static Flow Profitsmentioning
confidence: 99%
“…1 For related methods in the single agent context see Hotz and Miller (1993), Hotz et al (1994), and Aguirregabiria and Mira (2002). For a review of structural estimation of dynamic games see Ackerberg et al (in press).…”
Section: Static Flow Profitsmentioning
confidence: 99%
“…In the first stage, I use the Nested Pseudo Likelihood (NPL) algorithm developed in Aguirregabiria and Mira (2002) to obtain estimates of the model's dynamic parameters that characterize variable profits, along with the per-period fixed cost of operation. In the second stage, I use the Method of Simulated Moments (MSM) to recover estimates of the cost of entry and the parameters characterizing the distribution of unobserved potential entrant productivity.…”
Section: Résumémentioning
confidence: 99%
“…To estimate some of the dynamic parameters in the model below, I use the NPL algorithm developed in Aguirregabiria and Mira (2002), which offers a more efficient and parsimonious alternative to the estimators developed by Rust (1987) and Hotz and Miller (1993). 1 Collard-Wexler (2009) estimates a model of entry and exit using the multi-agent NPL algorithm developed in Aguirregabiria and Mira (2007) to study the role of plant productivity on turnover and profitability in the U.S. ready-mix concrete industry.…”
mentioning
confidence: 99%
“…For example, in 2003, the United States'Federal Communication Commission (FCC) amended the law and removed unbundling regulations on …ber-optic premises in order to accelerate building competition among carriers and promote investments in …ber networks, even though many companies without facilities objected. 2 However, in relation to unbundling regulation's importance, the literature that studies it is limited. This is because the municipal level data set is rarely available and building of the new networks, such as …ber-optic networks, is uncommon.…”
mentioning
confidence: 99%
“…Greenstein and Mazzeo (2006) found that unbundling widened the variety of services, and Economides, Seim and Viard (2008) found that competition in service markets induced 2 This deregulation has been continually criticized by …rms that use the regulated lines, and created a controversy between regulated …rms and the users of their facilities. For example, in December 2009, Cbeyond.Inc, supported by the Small Business Administration (SBA), …led a petition with the FCC to reverse the deregulation.…”
mentioning
confidence: 99%